Cytological diagnosis of unifocal Langerhans cell histiocytosis in the temporomandibular joint. - Tamiolakis, Dimitrios; Charizani, Aikaterini; Igoumenakis, Demosthenes; Volioti, Areti; Konsolaki, Eleni; Kalogeraki, Alexandra (Acta Biomedica Atenei Parmensis, 2022)
Unifocal Langerhans cell histiocytosis (LCH) presents as a solitary focal bone lesion characterized by clonal proliferation of CD1a (+) and langerin(+) dendritic cells, derived from the bone marrow. In 38-69% of cases BRAF-V600E mutation is revealed. It gains attention to maxillofacial surgeons due to involvement of the orofacial region and early onset of jaws symptoms. If overlooked, massive deconstruction of tissues, occurs.We present a case of LCH of the temporomandibular joint in a 14 aged child where fine needle aspiration favorably contributed in an accurate diagnosis combined with the appropriate clinicoradioliogical findings. This can overrule unwarranted biopsy and monitor the treatment largely where aproach to histopathology services is restricted.